The Limitations of Present Sensor Technology in Automotive Industry: A Review - Mohd Ali, Nursabillilah; Tee, DLY; Jian, KH; Wai, PT; Fang, LS; Hasan, Z; Ab Rashid, MZ; Razali, S (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
In the modern era of the 21st century, sensor technologies are springing up like mushrooms after the rain. Thus, this phenomenon had caused a variety of sensor technologies used in automotive in the present day. In this paper, we analyse the current sensor technologies used in the automotive field especially in the car which enable us to monitor our vehicles condition, to ensure our vehicle safety and lastly to ensure more significant driving comfort for both the driver and passengers. The types of sensors are presented, and the limitation of the sensors and its application in various systems are discussed in this paper.